Diagnostic and prognostic value of KRAS mutations in circulating pancreatic ductal adenocarcinoma tumor DNA - Yang, Xiaowei; Xu, Wei; Tian, Xiuyun; Wu, Jianhui; Lv, Ang; Li, Chengpeng; Guan, Xiaoya; Qian, Honggang; Hao, Chunyi (Translational Cancer Research, 2018)
Background: Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic tumor and one of the most malignant tumors worldwide. Circulating tumor DNA (ctDNA) has significant diagnostic and prognostic value for cancer patients. Methods: Surgical specimens and plasma samples were obtained from a total of 35 patients with PDAC at the Peking University Cancer Hospital between June 2016 and May 2017. To investigate KRAS mutations (G12R, G12V or G12D) in plasma ctDNA, digital polymerase chain reaction (PCR) was performed on samples obtained from PDAC patients before and after surgical resection. Results: KRAS mutations (G12R, G12V or G12D) between surgical tissue DNA (tDNA) and preoperative plasma ctDNA (pre-ctDNA) were consistent in 27 of 35 samples (77.1%, kappa index =0.397, P=0.003). Moreover, pre-ctDNA and postoperative plasma ctDNA (post-ctDNA) showed statistically significant associations with CA19-9 levels before surgery (P=0.027 and P=0.003, respectively). In addition, the Kaplan-Meier univariate and Cox multivariate analysis revealed that pre-ctDNA (G12V), post-ctDNA (G12V), or pre-post ctDNA (G12V, G12D) might be independent prognostic factors for overall survival (OS) and progression-free survival (PFS). Conclusions: Analysis of pre-ctDNA, post-ctDNA, and pre-post ctDNA showed high PDAC diagnostic and prognostic potential in patients.